Design and testing of a ground effect drone - Lim, Jia Wei (Nanyang Technological University, 2022)
Ground Effect (GE) Vehicles, otherwise known as WIGs (Wing in Ground-Effect Vehicles), are aircraft designed specifically to cruise at low chord-normalised ground clearances of less than 1 to reap the aerodynamic benefits of ground effect. However, practical concerns in GE vehicle design limit the extent to which the potential of ground effect can be realised. The objective of this FYP is to investigate the challenges in developing a GE vehicle for operation in extreme ground effect, which is observed for normalised ground clearances less than 0.1. To this end, a small-scale GE drone was sized using XFLR5 and built to a low take-off weight of 600g using a XPS foam fuselage and monocoque foam-core wings. Aerodynamic analyses of the GE drone were performed using wind tunnel testing and XFLR5. Obtained results show the alignment of lift predictions using XFLR5 with experimental data. Experimental results also align with all existing theoretical models in showing the increasing rate of lift increments when ground clearance is reduced. A potential 72% improvement in maximum lift to drag ratio was observed for the current GE drone when chord-normalised ground clearance was decreased from 1.4 to 0.6, and even greater improvements can be expected for GE drones designed to cruise in extreme ground effect. Flight tests were also performed but were inconclusive due to difficulties in conducting proper tests. In conclusion, this study found the design requirements for a water take-off to be a major challenge towards the development of an extreme ground effect drone as it is mutually incompatible with design requirements for a low operating ground clearance. Therefore, future GE drone designs may consider taking off from ground or vertically instead.